Pemetaan Perubahan Ruang Terbuka Hijau di Kecamatan Tanjungpinang Barat Tahun 2015 dan 2020 - Roziqin, Arif; Hansky, Premzky (Politeknik Negeri Batam, 2023)
Changing green open space has a direct impact on the needs of public places such as public public places in open environments. West Tanjungpinang District is a sub-district that has the highest population density among other sub-districts in Tanjungpinang City, so this also has an impact on changing the amount of green open space (RTH) as vegetation land cover. The result of reduced green open space is caused by changes in land use. So this study aims to map changes in the pattern of green open space to conditions and to find out the availability of open space in West Tanjungpinang. Therefore the method or method applied in this research is NDVI or Normalized Defference Vegetation Index. The NDVI method uses data from the Pleiades satellite imagery for 2020. The availability of green open space in Tanjungpinang Barat District still has an area value of above 30%, which in 2020 has an area of more than 4% or 0.178 km2. Changes in green open space in the 2015 Green Open Space pattern have decreased compared to 2020 green open space of 0.267 km2. This means that there is a change in the area of green open space that has been planned in 2015 in a span of 5 years or an area of 6% of the total area.